A method for obtaining the pure annihilation peak of Na-22 radioisotope - TAV, CUMALİ (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
By means of pulse separation technique, the annihilation gamma ray peak, which has great importance for positron annihilation lifetime spectroscopy (PALS), was discriminated from the superimposed photon spectrum generated by Compton effect, backscattering, and background in the 0.5 MeV energy region. Energy resolution of 4.5% was obtained for the discriminated annihilation peak of Na-22 positron emitter radioisotope. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: gamma ray spectroscopy; Na-22 and peak selection; positron annihilation radiation; PULSE-SHAPE DISCRIMINATOR